2019
DOI: 10.1371/journal.pone.0220953
|View full text |Cite
|
Sign up to set email alerts
|

COI metabarcoding primer choice affects richness and recovery of indicator taxa in freshwater systems

Abstract: Mixed community or environmental DNA marker gene sequencing has become a commonly used technique for biodiversity analyses in freshwater systems. Many cytochrome c oxidase subunit I (COI) primer sets are now available for such work. The purpose of this study is to test whether COI primer choice affects the recovery of arthropod richness, beta diversity, and recovery of target assemblages in the benthos kick-net samples typically used in freshwater biomonitoring. We examine six commonly used COI primer sets on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 54 publications
3
76
0
Order By: Relevance
“…Banzai in general annotated taxa more specifically than USEARCH and generated an order of magnitude higher number of OTUs, discussed below). Similarly, choice of metabarcoding marker and primer set biases results towards different sets of taxa [24]. Here, results from two different genetic markers, 18S and COI, revealed the same overall trends but with varying sensitivities to the taxa detected and the specificity of taxonomic annotations permitted by the genetic marker for different groups.…”
Section: Plos Onementioning
confidence: 58%
“…Banzai in general annotated taxa more specifically than USEARCH and generated an order of magnitude higher number of OTUs, discussed below). Similarly, choice of metabarcoding marker and primer set biases results towards different sets of taxa [24]. Here, results from two different genetic markers, 18S and COI, revealed the same overall trends but with varying sensitivities to the taxa detected and the specificity of taxonomic annotations permitted by the genetic marker for different groups.…”
Section: Plos Onementioning
confidence: 58%
“…However, multi-marker approaches do not guarantee better performance if reference databases are insufficiently populated or if primers impart amplification bias. The impact of these two factors on biodiversity inferences from eDNA metabarcoding has been explored (Hajibabaei et al, 2019;Kelly et al, 2019) but is inconsistently reported in field studies. Lecaudey et al (2019) detected only 23 of 43 fish species (53%) known to occur in their study area despite using three gene markers (cytb, 12S, 16S) in their analysis of Volga River eDNA samples.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, especially for indicator taxa, species or OTUs diversity was low. Li et al (2018) In the study by Hajibabaei et al (2019), which coined the term 'watered-down biodiversity', number of reads assigned to benthic invertebrates per eDNA sample was two orders of magnitude lower and diversity, measured as the number of exact sequence variants (ESVs) per sample, one order of magnitude lower compared to bulk samples. Pereira-da-Conceicoa et al (2019) showed that water samples from South African streams contained less than 10 % reads assigned to targeted macroinvertebrate taxa.…”
Section: Introductionmentioning
confidence: 99%